Isoalantolactone: a review on its pharmacological effects - Yang, Guang; Yang, Longfei; Xu, Fei (Frontiers in Pharmacology, 2024)
Isoalantolactone (ISA) is a sesquiterpene lactone that could be isolated from Inula helenium as well as many other herbal plants belonging to Asteraceae. Over the past two decades, lots of researches have been made on ISA, which owns multiple pharmacological effects, such as antimicrobial, anticancer, antiinflammatory, neuroprotective, antidepressant-like activity, as well as others. The anticancer effects of ISA involve proliferation inhibition, ROS overproduction, apoptosis induction and cell cycle arrest. Through inhibiting NF-κB signaling, ISA exerts its anti-inflammatory effects which are involved in the neuroprotection of ISA. This review hackled the reported pharmacological effects of ISA and associated mechanisms, providing an update on understanding its potential in drug development.